PENERAPAN DIGITAL BOOK SEBAGAI MODUL PEMBELAJARAN PADA MATA KULIAH KONSTRUKSI BANGUNAN I PENDIDIKAN TEKNIK BANGUNAN FAKULTAS TEKNIK UNIVERSITAS NEGERI JAKARTA - Daryati; Firdaus, Yusuf; Saleh, Rosmawita (LPPM, Universitas Negeri Jakarta, 2022)
This research departs from the problems that occur in the field, currently there are still many lecturers who have not used a variety of learning media, and according to the characteristics and needs of students in line with technological and IT developments. This study aims to find out how the application of the e-Learning Module learning media using E-Books as an interactive learning medium in the Building Construction 1 Course in the Building Engineering Education Study Program, UNJ, and its feasibility as an interactive learning medium in the Building Construction 1 Course in the Education Study Program. Building Engineering, UNJ. The research is using qualitative methods with the model of definition, design, and implementation. The research subjects were 2 lecturers and 63 students from the 2018-2019 class. The analysis used is descriptive analysis. The results of the study concluded that: (1) the application of the e-Learning Module learning media using E-Books as interactive learning media in the Building Construction I course at the Building Engineering Education Study Program, UNJ Jakarta was considered effective with a practical student percentage of 81.11% including the category very effective, especially used as online learning, and (2) the e-Learning module uses E-Books as interactive learning media in the Building Construction Course I at the Building Engineering Education Study Program, UNJ Jakarta which is very practical and feasible as an interactive learning medium in Building Construction I course at the Building Engineering Education Study Program, UNJ Jakarta, both based on the content of the material (88.50%), or based on the media aspect (83.33%), especially in online learning.